The Influence of Consumer Protection Policies on the Business Practices of E-commerce Companies: Case Studies in Online Markets - Loso Judijanto; Muhamad Taufik; Retno Sari Dewi; Syamsuddin Nur; Deng Jiao (Rechtsnormen: Journal of Law, 2024)
Background. The background of this research is driven by the rapid growth of the e-commerce industry, which has changed the business environment around the world. In this situation, consumer protection policies play an important role in regulating the business practices of e-commerce companies to protect the interests of consumers. However, it is possible that the implementation of such policies is not consistent or effective, raising questions about their actual influence on the business practices of e-commerce companies. Purpose. This research aims to thoroughly study how consumer protection policies affect the business practices of e-commerce companies, with a focus on case studies in online marketplaces. It is hoped that this research will gain a better understanding of the extent to which consumer protection policies encourage e-commerce companies to implement responsible and transparent business practices. Method. Primary data were collected through interviews or surveys with e-commerce companies operating in the online marketplaces selected as case studies. To support the results from primary data, secondary data, such as policy documents and company activity reports, were also analysed. Qualitative and quantitative analyses were conducted to find patterns and relationships between consumer protection policies and business practices of e-commerce companies. Results. Studies show that consumer protection policies influence the business practices of e-commerce companies in online marketplaces. Companies that follow these policies tend to implement more ethical business practices, such as ensuring clear product information, return policies, and handling consumer complaints. Conclusion. This research shows that the implementation and enforcement of consumer protection policies are critical to improving the business practices of e-commerce companies. E-commerce companies can build strong consumer trust, strengthen brand image, and guarantee sustainable growth in this competitive industry in the long run.